An oil production forecast for China considering economic limits. (15th October 2016) - Wang, Ke; Feng, Lianyong; Wang, Jianliang; Xiong, Yi; Tverberg, Gail E.
Abstract: In recent years, it has become apparent that oil prices may not rise endlessly. Unconventional oil is likely to be especially affected by low prices because it tends to be high-priced to extract. To estimate the impact prices might have on future Chinese oil production, we develop a model in which only future unconventional oil production is affected by price. We analyze three price scenarios: Stays Low, Best Estimate, and Ever-Rising Prices. In these scenarios, remaining Ultimate Recoverable Resources (URR) are estimated to be 10%, 50%, and 90% of remaining Technically Recoverable Resources, respectively. Since oil price can be expected to affect the shape of the extraction curve, we spread estimated URR to year using models that do not assume that future production will ultimately produce a symmetric Hubbert-type curve (Multi-Cycle Generalized Weng Model and Stochastic Resource-Constrained Growth Model). In the Best Estimate Scenario, China's oil production is expected to reach a maximum of 226.79 million tons in 2020. In the Ever-Rising Prices Scenario, China's maximum oil production occurs in 2023. In the Stays Low Scenario, maximum production has already been reached. Highlights: China's conventional oil reached a peak in 2010 and has begun to decline. Unconventional oil production will be especially adversely affected by low prices. Rising selling price of oil may lead to recession, bringing prices back down. China's total oil supply appears likely to peak about 2020. Likely oil production is less than Technically Recoverable Resources.